Correct solvability of the difference Pade schemes for parabolic equations in Holder spaces - Ashyraliev, A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We study Padé difference scheme for the approximate solution of the Cauchy problem for parabolic equations generated by the Padé fractions R_j,l, of exponential approximation. We establish an estimate of the coerciveness of the difference schemes for j=l-2, l-1, or even j=l in a smaller space than C_0^α(E).